The dynamics of motivation, emotion, and task performance in simulated achievement situations - Kiuru, Noona; Spinath, Birgit; Clem, Anna-Leena; Eklund, Kenneth; Ahonen, Timo; Hirvonen, Riikka (Learning and individual differences, 2020)
This study aimed to examine associations between motivation, emotion, and task performance in simulated achievement situations. A group of sixth grade students (n = 190) completed an achievement task. Situational information on task value, success expectations, emotions, effort, task performance, and causal attributions was collected and information on subsequent academic achievement was obtained from school registers. The results showed, first, that high task value, high expectancy of success, and high positive emotions before a task contributed to a higher level of effort during the task. This, in turn, was related to better task performance. Second, high expectancy of success predicted increased positive emotions during the task, and these in turn, were related to better task performance. Conversely, high negative emotions during the task were related to poorer task performance. Third, high task performance was related to higher levels of effort, higher attributions of success to ability, and increased positive emotions after the task. Finally, both high task performance and attributions of success to ability were related to better subsequent academic achievement.
Gesehen am 22.03.2021